(untitled) (Journal of Social Economics Research, 2025)
Commercial gambling is expanding in Kazakhstan amid digitalization and regulatory change, yet population-based estimates of participation and harm remain limited. This study provides a national baseline to inform product-specific harm-reduction policy. A cross-sectional, dual-language (Kazakh/Russian) survey of adults aged 18–60 (N = 1,015) was conducted in April–May 2025 using stratified quotas and post-stratification weights (sex, age, region) to generate population estimates. Measures included past-year gambling participation and intensity, the nine-item Problem Gambling Severity Index (PGSI; 12-month frame), and attitudes toward regulation and self-exclusion. Weighted proportions are reported for the full sample and, where relevant, past-year gamblers. An estimated 46.7% of adults (95% CI 43.6–49.8) gambled in the previous 12 months; 18.5% (95% CI 16.3–21.0) reported weekly or more frequent play. Among past-year gamblers (n = 474), 44.7% gambled weekly or more, 8.9% reported expenditure exceeding 50% of income, and 3.6% reported spending approximately all income on gambling. PGSI items indicating harm were frequently endorsed (e.g., chasing losses 82.5%; spending more than could be afforded 74.7%). Among non-gamblers, 68% viewed gambling “extremely negatively”; most favored strict regulation, with roughly three-quarters supporting a complete ban and about two-thirds endorsing mandatory youth risk education. Gambling in Kazakhstan is widespread, with substantial self-reported harm and strong public support for restrictive controls.